Enhancing the Compressive Strength and Density of Cement Mortar by the Addition of Different Alignments of Glass Fibers and Styrene Butadiene Rubber - Hamza, Mustafa M.; Fahad, Besma M. (Al-Khwarizmi Engineering Journal, 2017)
Abstract In the field of construction materials the glass reinforced mortar and Styrene Butadiene mortar are modern composite materials. This study experimentally investigated the effect of addition of randomly dispersed glass fibers and layered glass fibers on density and compressive strength of mortar with and without the presence of Styrene Butadiene Rubber (SBR). Mixtures of 1:2 cement/sand ratio and 0.5 water/cement ratio were prepared for making mortar. The glass fibers were added by two manners, layers and random with weight percentages of (0.54, 0.76, 1.1 and 1.42). The specimens were divided into two series: glass-fiber reinforced mortar without SBR and glass-fiber reinforced mortar with 7% SBR of mixture water. All specimens were tested after curing for 7 and 28 days, glass-fiber reinforced mortar exhibited better properties than control mortar in improvement of compressive strength and lowering the density after curing for 28 days due to the completion of cement hydration reaction.. For compressive strength the best results were achieved with 1.42 wt.% layers glass-fiber reinforced mortar with 7% SBR which gave 41.56 MPa. On the other hand, the addition of 1.42 wt.% random glass-fiber without SBR addition caused the beast reduction in density by 10.6% and produced lighter structure than control sample. Keywords: Random glass fibers , Glass fibers layers, SBR, compressive strength, density.